2022
DOI: 10.47230/unesum-ciencias.v6.n1.2022.667
|View full text |Cite
|
Sign up to set email alerts
|

Actualización en El Tratamiento Endoscópico Del Reflujo Vesicoureteral Primario en La Infancia

Abstract: El reflujo vesicoureteral (RVU) primario en la infancia predispone a las infecciones urinarias, cuando se trata de infecciones febriles recurrentes puede asociarse daño renal permanente. En un número considerable de casos la evolución natural de la enfermedad es hacia la resolución espontánea. En la actualidad existen varias opciones terapéuticas para el reflujo vesicoureteral, la selección del mismo debe ser individualizada. El objetivo de este trabajo es exponer aspectos generales y de actualidad sobre el tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The incidence of urinary tract infection in childhood varies between s, affecting 1 to 2% of boys and can increase up to 5% in girls. It is suggested that 25 to 70% of infants who suffer from recurrent febrile urinary tract infections are carriers of VUR 4,8 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of urinary tract infection in childhood varies between s, affecting 1 to 2% of boys and can increase up to 5% in girls. It is suggested that 25 to 70% of infants who suffer from recurrent febrile urinary tract infections are carriers of VUR 4,8 .…”
Section: Discussionmentioning
confidence: 99%
“…The exact prevalence of VUR is unknown, it is considered that one third of patients treated for urinary tract infection(UTI) are carriers of VUR. UTI occurs in between 5 and 10% of all children, in 20% of them the infection recurs, VUR is considered a predisposing factor for recurrence1.In Cuba this condition has an incidence of 1% in healthy children and 30 to 50% in children with UTI 4 . The association between VUR and urinary infection has been clearly established.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations